Produção de lipídeos e biomassa por mucorales (Mucor subtilíssimus UCP 1262, Cunninghamella echinulata UCP 1299 e Rhizopus microsporus UCP 1304) isolados da caatinga de Pernambuco - Silva, Miller da Costa Lima Batista e (2017)
Lipids obtained from microorganisms appear as a promising alternative for various industrial applications due to the innumerable advantages when compared to lipids derived from plant and animal sources. In this context, the objective of this work was to select Mucorales (Mucor subtilissimus, Cunninghamella echinulata and R. microsporus) fungi isolated from the Pernambuco Caatinga soil, which are potentially capable of producing biomass and lipids using alternative renewable sources. The cultivation of the Mucorales was carried out in means of production containing different concentration of sugarcane molasses and, different concentrations pH. From the selected medium, the strain with high potential to produce biomass and lipids was grown in new concentrations established from factorial planning. The yields of the biomass were calculated by gravimetry, the total lipids quantified after extraction by chloroform and methanol and the identification of the fatty acids was performed by gas chromatography (GC). Subsequently, a histochemical study was performed with the selected fungus. The data obtained showed that Cunninghamella echinulata was able to simultaneously produce high production of biomass (9,05g / L) and total lipids (46,96%) in a medium constituted by 10% of sugarcane molasses and 5% of corncina, With pH 6.0. From this selected medium, the results of the planning showed that the maximum production of biomass (10,1g / L) and lipids (47.86%) occurred in condition 4, in a medium constituted by maize (8%), cane molasses Of sugar (12%) and pH 6.0. In this way the data obtained show the high potential of Cunninghamella echinulata as a promising microorganism for the simultaneous production of biomass and lipids from renewable raw material, constituting an important technology to minimize environmental problems.